“Ivy Sign” on Fluid-Attenuated Inversion-Recovery Images in Childhood Moyamoya Disease - Maeda, Masayuki; Tsuchida, Chika (American Journal of Neuroradiology, 1999)
Summary: We report on MR studies of a 15-year-old girl with moyamoya disease in whom diffuse leptomeningeal enhancement (“ivy sign”) was revealed by fluid-attenuated inversion-recovery (FLAIR) and contrast-enhanced imaging. We speculate that the mechanism behind this enhancement is caused by a retrograde slow flow of engorged pial vasculature via leptomeningeal anastomosis. Nevertheless, it remains unknown whether the precise source of a high signal on FLAIR images is attributable to pial vessels themselves or congested thickening of the leptomeninges or both.